Synthesis and metal complexation of a schiff-base derivative of 2-amino-4-(p-tolyl)thiazole - Şekerci, M.; Alkan, C.; Çukurovali, A. (My University, 2000)
Thiazole Schiff-bases and their metal complexes have shown good biological activity. In this work, a Schiff base has been synthesized, from the reaction of 4-N,N-dimethylbenzaldehyde and 2-amino-4-(p-tolyl)thiazole. This compound was used as a complexing agent for Cu(II), Ni(II), and Co(II). The authenticity of the ligand and complexes was established by elemental analyses, UV-VIS, FT-IR, 'H-NMR, I3C-NMR, magnetic susceptibility measurements, TGA, and DTA. The nickel and cobalt compounds have square-planar and distorted octahedral structures while the copper compound has a tetrahedral structure.
Keywords: Co(ii) complexes; Cu(ii); Ni(ii); Schiff-base; Thiazole